Ginsberg Barańczaka. Z dziejów jed(y)nego przekładu - Meller, Oskar (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is an analysis of the translation of the poem A Supermarket in California (Supermarket w Kaliforni), the only poem by Allen Ginsberg translated by Stanisław Barańczak. In the critical works of the author of Facial Corrections (Korekta twarzy) the beatnik’s poetics is contrasted with the poetry of Robert Frost and James Merill – writers crucially important to the translator. Despite this, A Supermarket… enriched Barańczak’s anthology of American Poetry published in 1998. The translator’s key choice appears to be the use of a conversational idiom, placing the poem opposite the ‘howling’ diction from the flagship poems of the author of Howl. The testaments of a dialogue with tradition is what Barańczak seeks in it; he is most interested in the formal and semantic bows to the father of American poetry. What Barańczak makes the semantic dominant is, rather than the structure of the text or the images evoked in it, Whitman’s patronage with all its consequences.